Cohesive strength of nanocrystalline ZnO: Ga thin films deposited at room temperature - Samantilleke, A. P. (2011)
Transparent conducting nanocrystalline ZnO:Ga (GZO) films with electromechanical and electro-optical properties were deposited by dc magnetron sputtering at room temperature on polymers (and glass for comparison). Electrical resistivity of 8.8x10-4 and 2.2x10-3 Ω.cm was obtained for films deposited on glass and polymers respectively. The crack onset strain (COS), the cohesive strength of the coatings, as well as the influence of mechanical strain on the electrical properties were all investigated through tensile testing. The COS is similar for different GZO coatings and occurs for nominal strains ~1%. The cohesive strength of coatings, which was evaluated from the initial part of the crack density evolution, was found to be between 1.3 and 1.4 GPa. For these calculations, a Young´s modulus of 112 GPa was used, evaluated by nanoindentation.